Atrial involvement in arrhythmogenic right ventricular cardiomyopathy patients referred for ventricular arrhythmias ablation. (6th July 2018) - Wu, Lingmin; Bao, Jingru; Liang, Erpeng; Fan, Siyang; Zheng, Lihui; Du, Zhongpeng; Chen, Gang; Ding, Ligang; Zhang, Shu; Yao, Yan
Abstract: Background: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a heritable myocardium disorder that predominantly affects the ventricle. Little is known about atrial involvement. This study aimed to assess atrial involvement, especially the role of genotype on atrium in ARVC. Methods: The incidence, characterization and predictors of atrial involvement were investigated. Nine known ARVC‐causing genes were screened and the correlation between genotype and atrial involvement was assessed. Results: Right atrium (RA) dilation, left atrium (LA) dilation, and sustained atrial tachyarrhythmias (ATa) were found in 45, 16 and 3 patients, respectively. Gene mutations were identified in 64 (64.0%) patients. Mutation carriers showed more RA dilation than noncarriers (54.7% vs. 27.8%, P  = 0.009), and no difference in LA dilation and ATa. Multivariate analysis showed tricuspid regurgitation (OR: 18.867; 95% CI: 1.466‐250.000; P  = 0.024) increased the risk of RA dilation and decreased left ventricular ejection fraction (LVEF) (OR: 1.134; 95% CI: 1.002‐1.272; P  = 0.031) correlated with LA dilation, whereas genotype showed no significant effect. At a median follow‐up time of 91 months, 7 patients died and 1 patient accepted heart transplantation. New‐onset RA dilation, LA dilation, and sustained ATa were found in 8, 7, and 6 patients, respectively. Atrial involvement was not associated with the long‐term survival. Despite mutation carriers showing more RA dilation, Kaplan‐Meier analysis showed genotype was not associated with atrial involvement. Conclusion: Atrial involvement was common in ARVC. Tricuspid regurgitation and decreased LVEF increased the risk for atrial dilation. Genotype was not associated with atrial involvement.